Die nuwe Psalmomdigting: Die Messias weggelaat? - Van Rooy, H. F. (HTS teologiese studies, 2004)
The new Psalter in Afrikaans: Was the Messiah omitted?In 2001 a new Afrikaans metrical Psalter was published. Although beging severely criticised in som circles, it is being used by a number of churches. One of the major criticisms is that it omitted the Messiah from the Psalter, the implication being the way in which the so-called Messianic Psalms were treated in this Psalter, is cause for concern. This article discusses this criticism, provides a framework for dealing with the Messianic Psalms and evaluates the criticism. This criticism can not be regarded as valid. This Psalter tried to reflect the original context of the individual Psalms, refraining from using the New Testament’s use of the Psalms as a decisive factor for determining the original meaning.